Navigating the brain: How cerebral blood flow shifts with task complexity - Laura K. Fitzgibbon-Collins; Mamiko Noguchi; Geoff B. Coombs; Richard L. Hughson; Corey Guest; Robert Amelard; Dave McArthur; Sue Peters; Sarah Best; Michael Borrie; Habib Khan; J Kevin Shoemaker; et al. (PLoS ONE, 2025)
Monitoring middle cerebral artery blood velocity (MCAv) during maneuvers known to alter cerebral perfusion, such as supine-to-standing transitions or walking, may provide a more comprehensive assessment used to flag individuals susceptible to cerebral hypoperfusion in a way that cannot be achieved at rest. Furthermore, dual-tasks challenge the brain to match MCAv to meet increases in local demands of oxygen and energy in two different functional networks (motor and cognitive), potentially causing cerebral hypoperfusion when competing for shared and/or limited brain resources. We developed a dual-task paradigm comprising of five levels of task complexity, including single-tasks and dual-tasks. The main objective of the study was to evaluate changes in MCAv as task complexity increased, which was demonstrated through cognitive, motor, and combined cognitive-motor tasks in older adults with different cognitive function levels. A secondary objective was to assess the success rate (as a percentage) of obtaining MCAv signals during the dual-task protocol to determine the feasibility of measuring such metrics in older adults with varying levels of cognitive ability. Of the 88 participants (37 females, 75 ± 7 years, 27 ± 4 kg/m 2 ), a MCAv signal was ascertained in 56 participants throughout both single-tasks and both dual-tasks. MCAv increased when transitioning from a simple single-task to a more complex dual-task, while also highlighting a decline in motor and cognitive performance. A full multi-modal signal acquisition (MCAv, blood pressure, and cerebral oxygenation) was acquired for 48 participants. Lower MCAv signal acquisition was observed in females and people with cognitive impairment. We have demonstrated how MCAv changes with increased task complexity, while also uncovering declines in gait and cognitive performance. By establishing the feasibility of obtaining MCAv signals during cognitive stress tests and dynamic movements in older adults with varying cognitive abilities, we can begin to assess cerebral hypoperfusion using a potentially more sensitive indicator linked to neural damage.